Eat, pray, Love : One Woman's Search for Everything - Gilbert, Elizabeth (London Bloomsbury, 2010)
Elizabeth Gilbert was a burnt out journalist with her marriage in tatters when she left New York to visit Rome, India and Bali, seeking the three things that had been missing in her life: pleasure, devotion and balance. Slowly happiness began to creep up on her...This number one bestseller features a heartfelt and memorable narration by the author. It is now an acclaimed movie starring Julia Roberts. It's 3 a.m. and Elizabeth Gilbert is sobbing on the bathroom floor. She's in her thirties, she has a husband, a house, they're trying for a baby - and she doesn't want any of it. A bitter divorce and a turbulent love affair later, she emerges battered and bewildered and realises it is time to pursue her own journey in search of three things she has been missing: pleasure, devotion and balance. So she travels to Rome, where she learns Italian from handsome, brown-eyed identical twins and gains twenty-five pounds, an ashram in India, where she finds that enlightenment entails getting up in the middle of the night to scrub the temple floor, and Bali where a toothless medicine man of indeterminate age offers her a new path to peace: simply sit still and smile. And slowly happiness begins to creep up on her. This recording is unabridged. Typically abridged audiobooks are not more than 60 per cent of the author's work and as low as 30 per cent with characters and plotlines removed.
Keywords: Travel -- Self-Realization in Women